Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1097/01.hjh.0000242404.91332.be
|View full text |Cite
|
Sign up to set email alerts
|

Renal cathepsin G and angiotensin II generation

Abstract: This is the first time that cathepsin G has been identified in mammalian renal tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 38 publications
(38 reference statements)
0
30
0
Order By: Relevance
“…Alternatively, reabsorbed Agt may be transferred back to the tubular lumen and then converted to AII, or it may be processed to AII by lysosomal enzymes. 29 The present study does not determine how much of the renal AII is attributed to the Agt reabsorbed by proximal tubule cells as its precursor. To address this quantitative issue, mutant mice with 100% of proximal tubular cells carrying megalin null mutation need to be generated in view of our observation that, in mosaic megalin KOs, Agt protein incorporation of megalin gene intact cells becomes upregulated in a compensatory manner (Supplemental Figure 7).…”
Section: Discussionmentioning
confidence: 81%
“…Alternatively, reabsorbed Agt may be transferred back to the tubular lumen and then converted to AII, or it may be processed to AII by lysosomal enzymes. 29 The present study does not determine how much of the renal AII is attributed to the Agt reabsorbed by proximal tubule cells as its precursor. To address this quantitative issue, mutant mice with 100% of proximal tubular cells carrying megalin null mutation need to be generated in view of our observation that, in mosaic megalin KOs, Agt protein incorporation of megalin gene intact cells becomes upregulated in a compensatory manner (Supplemental Figure 7).…”
Section: Discussionmentioning
confidence: 81%
“…Already, there is ample evidence that such approaches can shed new light into even well studied subject areas such as the renin-angiotensin-system. Using MALDI-MES, Schlüter et al determined that renal Cathepsin G can generate angiotensin II 71 . Using the PALeO-assay, we demonstrated that endothelin-converting enzyme-1 (ECE-1), a member of the neprilysin protease family, can also generate angiotensin II (Figure 3) (M. Hardt, unpublished data, 2011).…”
Section: How To Gain Insights Into the Dynamics Of Proteolytic Procesmentioning
confidence: 99%
“…We have recently identified the presence of cathepsin B, a lysosomal cysteine protease that catalyses the conversion of pro-renin into active rennin (27, 28), cathepsin D, an aspartic lysosomal protease bearing significant homology to renin thus engages in renin-like actions of converting AGN to ATI (29, 30), and cathepsin G, a serine protease with the capacity to generate ATII from ATI and directly from AGN (31, 33), within proliferating infantile hemangioma (IH) (34). These cathepsin isozymes catalyze the production of angiotensin peptides without involvement of classical RAS cascade mechanisms and offer a potential explanation for the variable response of IH to treatment using RAS modulators such as β-blockers and ACE inhibitors (31). …”
Section: Introductionmentioning
confidence: 99%